Micronutrient deficiencies and plasmodium vivax malaria among children in the Brazilian Amazon - Benzecry, Silvana Gomes; Alexandre, Márcia Almeida A.Araújo; Vítor-Silva, Sheila; Salinas, Jorge L.; Melo, Gisely Cardoso de; Marinho, Helyde Albuquerque; Paes, Angela Tavares; Siqueira, Andre M.; Monteiro, Wuelton Marcelo; Lacerda, Marcus V. G.; Leite, Heitor Pons (PLoS ONE, 2016)
Background: There is a growing body of evidence linking micronutrient deficiencies and malaria incidence arising mostly from P. falciparum endemic areas. We assessed the impact of micronutrient deficiencies on malaria incidence and vice versa in the Brazilian state of Amazonas. Methodology/Principal Findings: We evaluated children <10 years old living in rural communities in the state of Amazonas, Brazil, from May 2010 to May 2011. All children were assessed for sociodemographic, anthropometric and laboratory parameters, including vitamin A, beta-carotene, zinc and iron serum levels at the beginning of the study (May 2010) and one year later (May 2011). Children were followed in between using passive surveillance for detection of symptomatic malaria. Those living in the study area at the completion of the observation period were reassessed for micronutrient levels. Univariate Cox-proportional Hazards models were used to assess whether micronutrient deficiencies had an impact on time to first P. vivax malaria episode. We included 95 children median age 4.8 years (interquartile range [IQR]: 2.3-6.6), mostly males (60.0%) and with high maternal illiteracy (72.6%). Vitamin A deficiencies were found in 36% of children, beta-carotene deficiency in 63%, zinc deficiency in 61% and iron deficiency in 51%. Most children (80%) had at least one intestinal parasite. During follow-up, 16 cases of vivax malaria were diagnosed amongst 13 individuals. Micronutrient deficiencies were not associated with increased malaria incidence: vitamin A deficiency [Hazard ratio (HR): 1.51; P-value: 0.45]; beta-carotene [HR: 0.47; P-value: 0.19]; zinc [HR: 1.41; P-value: 0.57] and iron [HR: 2.31; P-value: 0.16]). Upon reevaluation, children with al least one episode of malaria did not present significant changes in micronutrient levels. Conclusion: Micronutrient serum levels were not associated with a higher malaria incidence nor the malaria episode influenced micronutrient levels. Future studies targeting larger populations to assess micronutrients levels in P. vivax endemic areas are warranted in order to validate these results. © 2016 Benzecry et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Beta Carotene; Iron; Retinol; Trace Element; Zinc; Beta Carotene; Iron; Trace Element; Zinc; Beta Carotene Deficiency; Child; Controlled Study; Disease Surveillance; Female; Follow Up; Human; Infection Risk; Intestine Parasite; Iron Deficiency; Major Clinical Study; Male; Nutritional Assessment; Nutritional Deficiency; Nutritional Requirement; Parasite Identification; Parasite Incidence; Plasmodium Vivax Malaria; Retinol Deficiency; Rural Area; Zinc Deficiency; Blood; Complication; Deficiency; Isolation And Purification; Malaria, Vivax; Plasmodium Vivax; Child, Preschool; Proportional Hazards Model; Rural Population; Beta Carotene; Child; Child, Preschool; Female; Follow-up Studies; Humans; Iron; Malaria, Vivax; Male; Micronutrients; Nutrition Assessment; Plasmodium Vivax; Proportional Hazards Models; Rural Population; Vitamin A Deficiency; Zinc